(untitled) (Ius Novum, 2020)
This paper addresses the issue of jurisdictional independence of a disciplinary court in terms of the possibility of assessing an act under investigation in the context of the grounds of criminality of an act. The issue is of particular importance in view of the rules on limitation periods for disciplinary offences, which require the adoption of limitation periods for criminal offences where the act constitutes a criminal offence. Such a solution may lead to a conflict between the principle of jurisdictional independence of the disciplinary court and the principle of the presumption of innocence, since this presumption can only be rebutted by a final and non-appealable judgment of a criminal court. In turn, the stay of disciplinary proceedings and waiting for a final and non-appealable judgment of the criminal court may have a negative impact on the decision concerning the issue of disciplinary liability. This study proposes a compromise solution which, according to the author, would respect both principles.